2019
DOI: 10.2298/abs181213022d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toxicity and antioxidative effects of Tussilago farfara and Verbascum thapsus water extracts in zebrafish and in bronchial epithelial cells

Abstract: Tussilago farfara (coltsfoot) and Verbascum thapsus (mullein) have been used as folk remedies for treating respiratory disorders. The aim of this study was to test the toxicity of the water extracts of T. farfara and V. thapsus in vivo in zebrafish and in vitro in BEAS 2B epithelial bronchial cells. To the best of our knowledge, this is the first study to investigate the antioxidative properties of T. farfara and V. thapsus extracts in cell culture. Our results show that the T. farfara leaf extract does not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The ability with which metallic nanoparticles can destroy cancer cells partially depends on the stimulation of ROS in the damaged components of the cells [ 62 , 63 ]. The generation of a ROS response in both cell lines after AuNPsME treatments supports other findings indicating that the sole ME treatment alters the production of superoxide anion in selected cell lines [ 53 ]. Verbascum calvum flower extracts were assayed against human lung A549 and breast MCF-7 cancer cells, showing antiproliferative effects attributed to ROS generation and pro-inflammatory effects [ 64 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The ability with which metallic nanoparticles can destroy cancer cells partially depends on the stimulation of ROS in the damaged components of the cells [ 62 , 63 ]. The generation of a ROS response in both cell lines after AuNPsME treatments supports other findings indicating that the sole ME treatment alters the production of superoxide anion in selected cell lines [ 53 ]. Verbascum calvum flower extracts were assayed against human lung A549 and breast MCF-7 cancer cells, showing antiproliferative effects attributed to ROS generation and pro-inflammatory effects [ 64 ].…”
Section: Resultssupporting
confidence: 86%
“…Only a few reports have tested the safety of ME in selected models. For instance, Dragičevic et al [ 53 ] suggested that V. thapsus flowers aqueous extracts, prepared at 1:10 flower:water maceration, further rotary evaporator-mediated concentration up to 36 µg/mL, and dilutions starting from 1000× (0.036 µg/mL), did not induce malformations in zebrafish embryo, but viabilities in the range of 57.9–67.3% in human lung epithelial cells (BEAS-2B) suggested certain toxic effects that merit further research. Other authors reported that 50–200 µg/mL V. thapsus aqueous leaves extracts are safe in mice RAW264.7 macrophages and human adult chondrocytes (HC) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Same concentrations were used in single and combined treatments 5-FU/oxaliplatin (FOX) and 5-FU/irinotecan (FIRI). The decrease in cell viability by 50% under combined chemotherapeutic drug concentrations was confirmed by MTT assay according to previously described protocol [29]. SW620 cells were seeded in 6-well plates at 2 × 10 5 density and treated on the next day.…”
Section: Cultivation and Treatments Of Sw620 Cellsmentioning
confidence: 99%
“…However, the raw material studies from this plant showed that it contains hepatotoxic pyrrolizidine alkaloids (Adamczak et al, 2013). Dragicević et al (2019) have studied the evaluation of toxicity of Tussilago farfara water extracts in bronchial epithelial cells. Their results showed that T. farfara water leaf extract is potentially safe and beneficial in treating respiratory disorders such as asthma and suggested that its actions result from its antioxidative effects on bronchial epithelial cells.…”
Section: Tussilago Farfaramentioning
confidence: 99%